2022
DOI: 10.5114/wiitm.2022.114539
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction models for difficult cholecystectomy.

Abstract: Introduction In some cases, laparoscopic cholecystectomy (LC) may be very difficult and easily converted to laparotomy, causing many complications to patients and prolonging the prognosis time. Thus, to evaluate the difficulty of LC before operation is extremely important. Aim To explore the risk factors of difficult cholecystectomy (DC) and to establish a risk prediction model of DC. Material and methods The data of 201patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Obesity is a major patient factor which is known to be prevalent in patients who are eventually converted from LC to OC and our study reflected this as the majority (72.99%) of patients had a BMI above the norm, similar to Subhan, et al, Krishna, et al, and Chen G, et al [15,17,18]. Obese patients require consideration and counseling beforehand so that they can be involved in decision making prior to choosing a treatment modality.…”
Section: Discussionsupporting
confidence: 78%
“…Obesity is a major patient factor which is known to be prevalent in patients who are eventually converted from LC to OC and our study reflected this as the majority (72.99%) of patients had a BMI above the norm, similar to Subhan, et al, Krishna, et al, and Chen G, et al [15,17,18]. Obese patients require consideration and counseling beforehand so that they can be involved in decision making prior to choosing a treatment modality.…”
Section: Discussionsupporting
confidence: 78%
“…[15,36,37,43] Although there are models predicting difficulty, they are complex and not practical. [7][8][9][10]24,25,34,44,[44][45][46][47][48] . To predict the use of a bailout procedure in a more practical way, we estimated the area under the ROC curve of the time (minutes) spent trying to dissect the CD and found that it predicts the use of bailout techniques, as well as being a good predictor of conversion (see Graphs 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Possible reasons for the almost null use of prediction systems are implementation difficulties due to the complexity of such scales, making them impractical . [7][8][9][10] As prolongation of operative time is closely related to patient morbidity, most predictor scales include the time factor; however, while an experienced surgeon completes the cholecystectomy in >50% of his standard time, the values obtained do not apply to all. [11] Previous studies have documented that primary problems with Calot's triangle dissection are associated with difficulty; thus, hypothesizing that failure to complete Calot's triangle dissection within a predetermined period may be an early predictor of DLC and the development of complications.…”
Section: Introductionmentioning
confidence: 99%
“…Ewen and colleagues developed a scoring system for laparoscopic cholecystectomy that utilized the preoperative patient characteristics to predict surgical complexity. The system demonstrated positive predictive values of 90% and 88% for uncomplicated and complex cases, respectively 16 18 . However, effective tools for predicting the operative difficulty in TLH are insufficient.…”
Section: Introductionmentioning
confidence: 96%